Outcomes of failure of selective non-operative management of penetrating abdominal trauma - Almgla, Naser Khalifa (Division of General Surgery, 2023)
Background: Selective nonoperative management (SNOM) of penetrating abdominal trauma (PAT) is routine at our centre. The aim of this observational study is to report the outcomes of patients who have failed SNOM. Methods: All patients for the period (May 2015 – January 2018) who presented with penetrating abdominal trauma were reviewed. The patients were categorised into two groups: immediate laparotomy and delayed operative management (DOM) groups. The outcomes of the two groups were compared in terms of postoperative complications as a primary outcome, mortality and length of hospital stay as secondary outcomes. Results: A total of 944 patients with PAT were managed over the 33-month study period. After excluding 100 patients undergoing damage control surgery; 402 (47.6%) and 542 (52.4%) patients were treated with SNOM and immediate laparotomy, respectively. In the NOM cohort, 359 (89.3%) were managed successfully without laparotomy. Thirty-seven (86.0%) patients in the DOM group had a therapeutic laparotomy and six (14.0%) had an unnecessary laparotomy. Nine (20.9%) patients in the DOM group developed complications. There was no significant difference in the complication rates between the immediate laparotomy and DOM group. The hospital length of stay (LOS) was comparable between the two groups. There was no mortality reported in the SNOM group. Conclusion: Delayed laparotomy for PAT in patients initially selected for NOM, irrespective of mechanism, results in morbidity, mortality and hospital stay comparable to those who underwent immediate laparotomy.